A Literature Review of Action Research Trends and Innovations for Teaching Physics in the Philippines - Andrin, Arnel R.; Adlaon , Mauricio S. (Tecno Scientifica Publisher, 2026)
This systematic literature review examined how action research was used to address persistent challenges in physics education in the Philippines. Physics education played a key role in building scientific literacy, critical thinking, and problem-solving skills—competencies emphasized by the K to 12 curriculum under Republic Act No. 10533 and reinforced by DepEd Order No. 16, s. 2017, which promoted teacher-led research. The urgency for pedagogical innovation intensified during the COVID-19 pandemic, which disrupted traditional teaching and exposed limitations in laboratory access, digital readiness, and student engagement. Despite these developments, there had been no comprehensive synthesis of empirical studies documenting how action research supported physics instruction in the Philippine context. This review addressed that gap by consolidating findings from 14 peer-reviewed studies published between 2021 and 2025, identified through a PRISMA 2020, guided search across Scopus, Web of Science, Google Scholar, ERIC, and ScienceDirect. Qualitative thematic analysis revealed four dominant trends: experiential simulations and inquiry-based models that actively engaged learners in conceptual exploration and problem-solving; integration of technological tools such as PhET simulations, mobile learning platforms, and video-based instruction to enhance accessibility and interactivity; cultural contextualization, including the incorporation of indigenous games and ethno-STEM approaches to increase relevance and inclusivity; and gamification to promote motivation, collaboration, and sustained participation, particularly in underserved communities. These innovations demonstrated positive effects on student engagement, achievement, and teacher professional growth, yet challenges persisted. These included inadequate institutional support for sustained research, unequal access to technology, and difficulties in aligning innovations with standardized curricula. The review concluded that action research offered a systematic, evidence-based mechanism for refining teaching strategies, fostering reflective practice, and sustaining innovation. The findings provided a foundation for enhancing teacher training, shaping education policy, and promoting broader adoption of learner-centered, context-sensitive approaches in physics education.